DESENVOLVIMENTO, CARACTERIZAÇÃO E ATIVIDADE ANTIFÚNGICA FRENTE À Glomerella cingulata DE NANOEMULSÕES CONTENDO MANCOZEBE E EUGENOL - Oliveira, Daniela Alves de (2017)
Viticulture in Brazil has a great economic importance and an extension of approximately 80,000 hectares, generating employment and income for several families, however it is quite prone to infectious processes, which drastically reduces its productivity. Among these agents is Glomerella cingulata, which is controlled by fungicides, such as mancozeb. However, the use of this commercial product is related to contamination of the environment, in addition to a known toxic effect for humans. In this context the use of a naturally occurring substance, such as eugenol, could be a promising alternative. However, eugenol, which has an antimicrobial action, presents high volatilization and low solubility in water, thus impairing its administration and efficacy. One possibility to minimize toxicity of the fungicide, and the instability of eugenol, is nanoencapsulation. Therefore, the aim of this work was to verify the feasibility of co-encapsulation of mancozeb and eugenol in nanoemulsions and to evaluate the potential antifungal activity of nanoemulsions containing these compounds isolated and associated with Glomerella cingulata. Nanoemulsions containing eugenol (NE-E), mancozeb and eugenol (NE-ME), nanoemulsions with mancozeb (NE-M) and white nanoemulsions, without the active ones (NE-B) were prepared by the spontaneous emulsification method. The formulations were characterized according to mean diameter, polydispersity index (PDI), zeta potential, pH, content and morphology. The stability of the formulations for 30 days under different storage conditions and the antifungal activity against G. cingulata were also evaluated. The nanoemulsions had a mean diameter of approximately 200 nm, PDI of approximately 0.170, zeta potential of -11.0 mV, pH close to 5.0 and eugenol content, for NE-E and NE-ME, around 40%. Transmission electron microscopy showed spherical shape. The antifungal activity assay was performed by the macrodilution technique, and the active compounds were analyzed: free eugenol, mancozeb, mancozeb and eugenol and the same nanoencapsulated ones. The NE-M obtained a minimum inhibitory activity of 0.009 μg / mL, a satisfactory result, followed by NE-ME 0.02 μg / mL mancozeb + 2 μg/mL eugenol compared to its free forms. The best condition for storage of the formulations was under refrigeration and antifungal activity was potentiated after nanoencapsulation for all formulations. This study presents an innovative alternative for the treatment of G. cingulata through the use of nanotechnology.